THE INFLUENCE OF DANGDUT MUSIC TO THE BEHAVIOR OF CHILDREN SCHOOL AGE YEAR IN INDONESIA: A LITERATURE REVIEW - Bety Agustina Rahayu; Iman Permana (Department of Nursing, Faculty of Health Sciencce, Universitas Brawijaya, 2019)
Dangdut music is popular music for some people in Indonesia, especially those from the middle-low socioeconomic group, popular not only for adults but also children, sometimes the lyrics for adults are accompanied by unrestricted visual effects watched by children. The aimed of this study was to the reviewing literature related to the influence of dangdut music on deviations in child behavior. Searching for literature on databases in ProQuest, DOAJ, EBSCO, Pubmed, IPI Google School and Google Education with a range from 2013 to 2017. Using keywords